Cryoballoon ablation guided by a novel wide-band dielectric imaging system - Rottner, Laura; Obergassel, Julius; My, Ilaria; Kirchhof, Paulus; Ouyang, Feifan; Reissmann, Bruno; Metzner, Andreas; Rillig, Andreas (Frontiers in Cardiovascular Medicine, 2022)
Background and aim To investigate the feasibility, acute efficacy, periprocedural safety, and procedural parameters of CB-based PVI guided by KODEX-EPD using different occlusion tool software versions. Methods and results A total of 173 patients (60/173 (35%) paroxysmal AF, 64 ± 12 years, 66/173 (38%) female), underwent CB-based PVI guided by KODEX-EPD between August 2019 and October 2021. Acute PVI was achieved in all the patients. Total fluoroscopy time and dye volume were 13.9 [10.6–19.4] min and 47.5 [20–70] ml. Periprocedural complications occurred in 3 (2%) of the 173 patients. As part of the continued development program, different software versions were used, including 1.4.6 on 38 (22%), 1.4.6a on 33 (19%), 1.4.7 on 41 (24%), and 1.4.8 on 61 (35%) of the patients. Outcomes were compared between software versions by a univariate analysis. Sensitivity analyses were performed to account for confounders. Median fluoroscopy time was decreased by 6.4 min (37.3%), and the median volume of dye was decreased by 32.5 ml (52%) from versions 1.4.6 to 1.4.8. Software version was a significant predictor of fluoroscopy time and dye volume, while reductions in procedure duration and dose area product were observed but mainly explained via confounders. Conclusion CB-based PVI guided by KODEX-EPD is feasible and safe. Progressive software improvements appear to be associated with lower fluoroscopy duration and dye use. Further studies are needed to evaluate the advantage of KODEX-EPD-guided compared to conventional CB-PVI.